Klusterisasi Penyandang Masalah Kesejahteraan Sosial (PMKS) Di Kabupaten Bojonegoro Menggunakan Algoritma K-Medoids - Elisa Syafaqoh; Nurissaidah Ulinnuha; Lutfi Hakim (KUBIK, 2022)
Persons with Social Welfare Problems (PMKS) are individuals, community groups, or families who cannot adequately and properly meet their economic, physical, mental, and social needs, both spiritually and physically, because of an obstacle, difficulty, or disturbance. This study aimed to classify sub-districts in Bojonegoro Regency based on the level of social welfare problems using the K-Medoids Clustering (PAM) Analysis method. There are 2 clusters formed with an Average Silhouette of 0.73. Cluster 1 is a sub-district group with common social welfare problems, and Cluster 2 is a sub-district group with high social welfare problems. Each silhouette value of the cluster is 0.74 and 0.70 with the specifications of a well-formed and strong structure.